PENERAPAN DOSIS DAN LAMA FERMENTASI OLEH KAPANG TRICHODERMA VIRIDE TERHADAP KANDUNGAN SERAT KASAR DAN TANIN PADA TONGKOL JAGUNG - L. S. Enawati (Politeknik Pertanian Negeri Kupang, 2016)
A studies have been conducted in Almira Kupang, East Nusa Tenggara on fermented corn cob with fungi Trichoderma viride, in order to determine the content of tannins and crude fiber corncobs after fermentation by treatment dosage and duration of molds fermentation. The study was designed using a completely randomized design (CRD) patterned with a 4x5x3 factorial. The main factor was the dose of mold (D),having 0; 2.5; 5 and 7.5 g/ kg and the second factor was the period of the fermentation time (W), having 0, 4, 8,12 and 16 days; and 3 replications each. The results showed a significant effect of treatment (P<0.05) on tannin and crude fiber content in fermented corn cob.The treated combination of D7,5-W12 was the best treatment to decrease tannins content from 12.75% to 5.18% and crude fiber content from 20.54% to 35.67%. Thus the best fermentation results were shown on the application of the fungus Trichoderma viride at the dose of 7.5 g/ kg fermented for 12-days. It is recommended to do further research feeding animals with the feremented corn cob, especially ruminants.Keywords: Corn Cobs, Trichoderma viride, Tannin, Crude Fiber